An Atypical Case of Monomicrobial Clostridioides difficile Septicemia With No Gastrointestinal Manifestations - Wang, Liqian; Li, Danyang; Chen, Zixi; He, Liuqing; Wang, Xianjun; Tao, Liang (Frontiers in Cellular and Infection Microbiology, 2022)
An uncommon case of monomicrobial Clostridioides difficile septicemia in a 63-year-old man was reported in Zhejiang, China. Once diagnosed, vancomycin treatment cleared the infections. The patient had no remarkable medical history, and the inspection showed no overt gastrointestinal symptoms, though C. difficile was detected in his stool samples. However, we later defined that the C. difficile strain isolated from the blood sample was different from the one isolated from his stool using the whole genome sequencing analysis. By retrospective analysis of his medical record, we noticed that the man had a recent tooth extraction thus the bacterium may have invaded through the root canal. Therefore, we suggest that oral C. difficile colonization may be a potential risk factor for severe C. difficile septicemia, which could be clinically alarming.